2013
DOI: 10.3349/ymj.2013.54.1.209
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Venous Air Embolism during Myomectomy: The Effect of Patient Position

Abstract: PurposeVenous air embolism (VAE) is characterized by the entrainment of air or exogenous gases from broken venous vasculature into the central venous system. No study exists regarding the effect of patient positioning on the incidence of VAE during abdominal myomectomy. The purpose of this study was to assess the incidence and grade of VAE during abdominal myomectomy in the supine position in comparison to those in the head-up tilt position using transesophageal echocardiography.Materials and MethodsIn this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Previous studies on GE during hysteroscopic surgery have mainly focused on the incidence of GE; the influence of surgical location, surgical instruments, and anesthetics; and the monitoring of GE 5,7–10 . Intriguingly, in our clinical observation, we found that GE did not occur when patients were administered 100% oxygen, but different degrees of GE occurred when 50% oxygen was inhaled with the same surgical instruments and surgical personnel.…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…Previous studies on GE during hysteroscopic surgery have mainly focused on the incidence of GE; the influence of surgical location, surgical instruments, and anesthetics; and the monitoring of GE 5,7–10 . Intriguingly, in our clinical observation, we found that GE did not occur when patients were administered 100% oxygen, but different degrees of GE occurred when 50% oxygen was inhaled with the same surgical instruments and surgical personnel.…”
Section: Introductionsupporting
confidence: 50%
“…Previous studies on GE during hysteroscopic surgery have mainly focused on the incidence of GE; the influence of surgical location, surgical instruments, and anesthetics; and the monitoring of GE. 5,[7][8][9][10] Intriguingly, in our clinical observation, we found that GE did not occur when patients were administered 100% oxygen, but different degrees of GE occurred when 50% oxygen was inhaled with the same surgical instruments and surgical personnel. A study comparing the effects of 100% oxygen, 50% oxygen in nitrogen, and 50% oxygen in nitrous oxide controlled ventilation on venous air embolization responses in pigs indicated a small hemodynamic change after venous air embolism in the 100% oxygen group, which suggested that 100% inspiratory oxygen is preferable to oxygen in air for surgeries with a high risk of venous air embolism.…”
mentioning
confidence: 48%